2015
DOI: 10.1093/cvr/cvv097
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mPTP activation mechanisms in ischaemia–reperfusion: contributions of Ca2+, ROS, pH, and inorganic polyphosphate

Abstract: Transient Ca(2+)/polyP-mediated mPTP opening during ischaemia may serve to protect cells against cytosolic Ca(2+) overload, whereas ROS/pH-mediated sustained mPTP opening on reperfusion induces cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 63 publications
6
120
0
4
Order By: Relevance
“…The lack of PTP re-opening as [Ca 2+ ] mito recovers might also be due to loss of mitochondrial Ca 2+ bound phosphate and polyphosphate, that may both promote PTP opening. 21, 35 Hence, tPTPs may also reset mitochondrial Ca 2+ buffering in a way that restores acute responsiveness of Ca-dependent dehydrogenase activation during cytosolic Ca 2+ changes, while limiting further PTP events.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of PTP re-opening as [Ca 2+ ] mito recovers might also be due to loss of mitochondrial Ca 2+ bound phosphate and polyphosphate, that may both promote PTP opening. 21, 35 Hence, tPTPs may also reset mitochondrial Ca 2+ buffering in a way that restores acute responsiveness of Ca-dependent dehydrogenase activation during cytosolic Ca 2+ changes, while limiting further PTP events.…”
Section: Discussionmentioning
confidence: 99%
“…The cell dish was assembled with closed perfusion cell culture dish inserts (Warner Instrument) for solution changes during recording and then mounted onto the stage of a confocal microscopy (Nikon A1R). TMRM fluorescence (λ em 552 nm and λ ex 543 nm) was first recorded in oxygenated Tyrode buffer for 6 min as baseline and then simulated ischemia was initiated by exchanging normal Tyrode buffer with a simulated ischemia buffer containing (in mM) 20 2-deoxyglucose, 2 NaCN, 135 NaCl, 4 KCl, 1 MgCl 2 , 2 CaCl 2 , and 10 Hepes, pH 6.4 [38,40] through the inlet and outlet ports of the perfusion cell culture dish inserts. After 10 min incubation in simulated ischemia buffer, restoration of the control conditions was initiated by suffusing the cells with normal Tyrode buffer through the cell culture dish inserts over 8 min to wash out the simulated ischemia buffer.…”
Section: Methodsmentioning
confidence: 99%
“…After the biochemical changes that occur during ischemia (increase in ROS, Ca 2ϩ , and P i levels and decrease in ATP content and membrane potential), the mPTP was primed but remained closed because of the low intracellular pH. More recently, Seidlmayer et al (168) demonstrated that cardiac ischemia is associated with transient mPTP opening to protect cells from Ca 2ϩ accumulation and ROS production (Fig. 3).…”
Section: Chronology Of Events At the Level Of Skeletal Muscle Fiber Cmentioning
confidence: 96%
“…In parallel, ischemia participates in production of ROS, mainly O 2 ·Ϫ and H 2 O 2 (5,159,168). Few studies have examined the effects of ischemia alone in skeletal muscle by measuring either ROS production directly or oxidative stress products.…”
Section: Chronology Of Events At the Level Of Skeletal Muscle Fiber Cmentioning
confidence: 99%
See 1 more Smart Citation